Co-modulation of TNFR1 and TNFR2 in an animal model of multiple sclerosis - Timon Fiedler; Richard Fairless; Kira Pichi; Roman Fischer; Fabian Richter; Roland E. Kontermann; Klaus Pfizenmaier; Ricarda Diem; Sarah K. Williams (Journal of Neuroinflammation, 2023)
Abstract Background Tumour necrosis factor (TNF) is a pleiotropic cytokine and master regulator of the immune system. It acts through two receptors resulting in often opposing biological effects, which may explain the lack of therapeutic potential obtained so far in multiple sclerosis (MS) with non-receptor-specific anti-TNF therapeutics. Under neuroinflammatory conditions, such as MS, TNF receptor-1 (TNFR1) is believed to mediate the pro-inflammatory activities associated with TNF, whereas TNF receptor-2 (TNFR2) may instead induce anti-inflammatory effects as well as promote remyelination and neuroprotection. In this study, we have investigated the therapeutic potential of blocking TNFR1 whilst simultaneously stimulating TNFR2 in a mouse model of MS. Methods Experimental autoimmune encephalomyelitis (EAE) was induced with myelin oligodendrocyte glycoprotein (MOG35-55) in humanized TNFR1 knock-in mice. These were treated with a human-specific TNFR1-selective antagonistic antibody (H398) and a mouse-specific TNFR2 agonist (EHD2-sc-mTNFR2), both in combination and individually. Histopathological analysis of spinal cords was performed to investigate demyelination and inflammatory infiltration, as well as axonal and neuronal degeneration. Retinas were examined for any protective effects on retinal ganglion cell (RGC) degeneration and neuroprotective signalling pathways analysed by Western blotting. Results TNFR modulation successfully ameliorated symptoms of EAE and reduced demyelination, inflammatory infiltration and axonal degeneration. Furthermore, the combinatorial approach of blocking TNFR1 and stimulating TNFR2 signalling increased RGC survival and promoted the phosphorylation of Akt and NF-κB, both known to mediate neuroprotection. Conclusion These results further support the potential of regulating the balance of TNFR signalling, through the co-modulation of TNFR1 and TNFR2 activity, as a novel therapeutic approach in treating inflammatory demyelinating disease.